3D bioprinting of dECM-incorporated hepatocyte spheroid for simultaneous promotion of cell-cell and -ECM interactions - Kim, Min Kyeong; Jeong, Wonwoo; Jeon, Seunggyu; Kang, Hyun-Wook (Frontiers in Bioengineering and Biotechnology, 2023)
The cell spheroid technology, which greatly enhances cell-cell interactions, has gained significant attention in the development of in vitro liver models. However, existing cell spheroid technologies still have limitations in improving hepatocyte-extracellular matrix (ECM) interaction, which have a significant impact on hepatic function. In this study, we have developed a novel bioprinting technology for decellularized ECM (dECM)-incorporated hepatocyte spheroids that could enhance both cell-cell and -ECM interactions simultaneously.To provide a biomimetic environment, a porcine liver dECM-based cell bio-ink was developed, and a spheroid printing process using this bio-ink was established. As a result, we precisely printed the dECM-incorporated hepatocyte spheroids with a diameter of approximately 160-220 μm using mouse primary hepatocytes (PMHs). The dECM materials were uniformly distributed within the bio-printed spheroids, and even after more than two weeks of culture, the spheroids maintained their spherical shape and high viability. The incorporation of dECM also significantly improved the hepatic function of hepatocyte spheroids. Compared to hepatocyteonly spheroids, dECM-incorporated hepatocyte spheroids showed approximately 4.3-and 2.5fold increased levels of albumin and urea secretion, respectively, and a 2.0-fold increase in CYP enzyme activity. These characteristics were also reflected in the hepatic gene expression levels of ALB, HNF4A, CPS1, and others. Furthermore, the dECM-incorporated hepatocyte spheroids exhibited up to a 1.8-fold enhanced drug responsiveness to representative hepatotoxic drugs such as acetaminophen, celecoxib, and amiodarone. Based on these results, it can be concluded that the dECM-incorporated spheroid printing technology has great potential for the development of highly functional in vitro liver tissue models for drug toxicity assessment.